2019
DOI: 10.3390/pr7090550
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Computational Methods for Clustering Genes with Similar Biological Functions

Abstract: Clustering techniques can group genes based on similarity in biological functions. However, the drawback of using clustering techniques is the inability to identify an optimal number of potential clusters beforehand. Several existing optimization techniques can address the issue. Besides, clustering validation can predict the possible number of potential clusters and hence increase the chances of identifying biologically informative genes. This paper reviews and provides examples of existing methods for cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 114 publications
(205 reference statements)
1
13
0
Order By: Relevance
“…The previous studies confirmed the proper results of these two methods in the diseases diagnosis and patterning based on gene expression data (Grotkjaer et al, 2006). According to previous studies, k-means is the most well-known method clustering although it suffers from identifying the number of clusters beforehand (Hand and Heard, 2005;Ciaramella and Staiano, 2019;Nies et al, 2019). This fact may lead to poor performance of k-means in gene expression data clustering (Nies et al, 2019).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The previous studies confirmed the proper results of these two methods in the diseases diagnosis and patterning based on gene expression data (Grotkjaer et al, 2006). According to previous studies, k-means is the most well-known method clustering although it suffers from identifying the number of clusters beforehand (Hand and Heard, 2005;Ciaramella and Staiano, 2019;Nies et al, 2019). This fact may lead to poor performance of k-means in gene expression data clustering (Nies et al, 2019).…”
Section: Discussionsupporting
confidence: 52%
“…Since cancer is a complex disease, it is influenced by various factors, such as upregulation of predisposing factors and downregulation of growth-inhibiting factors which ultimately lead to tumor growth and metastasis. Meanwhile, helpful information about genes or disease pattern could be obtained by comparison of gene expression algorithms under different conditions such as diverse tissues, blood specimens and different growing environments (Hand and Heard, 2005;Ciaramella and Staiano, 2019;Nies et al, 2019). All the genes selected in this study had prominent roles in the control of the activity of the immune system, as well as the chemotaxis, angiogenesis, apoptosis, and so forth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HEED achieves a connected multi-hop inter-cluster network that maximizes the network lifetime for a determined density model and a specified relation between cluster range and transmission range hold. In [ 17 ], Nies et al provided an overview on computational algorithms for genes clustering with correlated biological functions. Different clustering categories have been summarized, where the pros and cons of each category have been discussed.…”
Section: Literature Reviewmentioning
confidence: 99%